Mating Status Influences Cold Tolerance and Subsequent Reproduction in the Invasive Ladybird Harmonia axyridis - Facon, Benoit; Estoup, Arnaud; Hufbauer, Ruth A.; Foucaud, Julien; Tayeh, Ashraf (Frontiers in Ecology and Evolution, 2017)
Among arthropods, ability to survive cold conditions may be instrumental for species invading temperate or colder climatic zones. Cold tolerance can be influenced by multiple environmental and physiological factors. We experimentally investigated the effects of mating status (unmated, mated, or mated, and reproductive) on cold tolerance and subsequent reproduction of the invasive harlequin ladybird Harmonia axyridis. We found that unmated adults survived cold better than mated ones. Among mated individuals, those that had not reproduced survived better than those that had reproduced. After cold stress, formerly unmated females were mated, and we evaluated their ability to reproduce. Females that reproduced prior to cold stress were less likely to reproduce after cold stress than females from the other treatments. We discuss what these results mean for the proportion of unmated females in H. axyridis aggregates at overwintering sites. This study highlights the importance of physiological status on cold tolerance of invasive arthropods.